FRI0134 A PHASE 3 STUDY OF THE EFFICACY AND SAFETY OF PEFICITINIB (ASP015K) IN PATIENTS WITH RHEUMATOID ARTHRITIS WHO HAD AN INADEQUATE RESPONSE TO DMARDS. (June 2019) - Tanaka, Yoshiya; Takeuchi, Tsutomu; Tanaka, Sakae; Kawakami, Atsushi; Iwasaki, Manabu; Song, Yeong Wook; Chen, Yi-Hsing; Rokuda, Mitsuhiro; Izutsu, Hiroyuki; Ushijima, Satoshi; Kaneko, Yuichiro; Shiomi, Teruaki; et al.
Abstract : Background: Peficitinib (ASP015K), a novel oral JAK inhibitor, demonstrated efficacy as once-daily monotherapy in patients with moderate to severe rheumatoid arthritis (RA) in a phase 2b study (NCT01649999 ). Objectives: To evaluate the efficacy and safety of peficitinib alone or in combination with disease-modifying antirheumatic drugs (DMARDs) in patients with RA who had an inadequate response to DMARDs. Methods: This multicentre, randomised, double-blind, parallel-group, placebo (PBO)-controlled phase 3 study (NCT02308163 ) was conducted in Japan, Korea and Taiwan. All patients had RA diagnosed according to 1987 ACR or 2010 ACR/EULAR criteria. Patients with active RA (defined as ≥6 tender and painful joints and ≥6 swollen joints, using 68 and 66-joint assessment respectively, and CRP >0.50 mg/dL) and inadequate response to DMARDs (administered for ≥90 days) were randomised in a 1:1:1:2 ratio to 52 weeks' treatment with PBO, peficitinib 100 mg/day, peficitinib 150 mg/day or etanercept 50 mg/week (open-label reference arm). At week 12, patients initially assigned to PBO were switched (under blinded conditions) to either peficitinib 100 mg/day or peficitinib 150 mg/day until end of treatment. Concomitant stable dose of DMARDs was permitted. The primary efficacy variable was ACR20 response rate at week 12/early termination (ET). Results: In total, 507 patients were randomised and treated: PBO (n=101), peficitinib 100 mg/day (n=104), peficitinib 150 mg/day (n=102) and etanercept (n=200). Regarding efficacy at week 12/ET, significant differences were observed with peficitinib 100 mg/150 mg vs PBO (p<0.001) in the proportion of patients achieving ACR20, ACR50, ACR70 (150 mg/day dose only) and DAS28-CRP <2.6, and for change from baseline to week 12/ET in DAS28-CRP (Table 1 ). Week 0–12 safety results were similar between treatment groups and serious adverse events were more common with PBO than other study treatments (Table 2 ). For the overall study period, the incidence rate of serious infections per 100 patient-years was higher with peficitinib 100 mg/150 mg than PBO (Table 2 ). There were no deaths during the study. Conclusion: In patients with RA who had an inadequate response to DMARDs, 100 mg/day and 150 mg/day peficitinib doses significantly reduced RA symptoms according to clinical and patient assessment scores. The proportion of patients achieving the primary efficacy variable (ACR20 at week 12/ET) was significantly greater for both peficitinib doses versus PBO. Peficitinib 100 mg/day and 150 mg/day showed acceptable safety and tolerability, with no new safety signals detected compared with other JAK inhibitors. Acknowledgement: This study was sponsored by Astellas Pharma, Inc. Medical writing support was provided by Rhian Harper Owen of Cello Health MedErgy and funded by Astellas Pharma, Inc. Disclosure of Interests: Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics, Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K., Sakae Tanaka Grant/research support from: KYOCERA Corporation and Asahi Kasei Corporation, Consultant for: Amgen Astellas BioPharma K.K., KYOCERA Corporation, Pfizer and Daiichi Sankyo Co., Ltd., Speakers bureau: Asahi Kasei Corporation, Astellas Pharma Inc, Ayumi Pharmaceutical Corporation, Eisai Co., Ltd., Ono Pharmaceutical Co., Ltd., Daiichi Sankyo Co., Ltd, Taisho Toyama Pharmaceutical Co., Ltd., Mitsubishi Tanabe pharma Corporation, Chugai Pharmaceutical Co., Ltd., Teijin Pharma Ltd., Eli Lilly, Hisamitsu Pharmaceutical Co, Inc., Pfizer, Bristol-Myers., Atsushi Kawakami Grant/research support from: Astellas Pharma, Consultant for: Astellas Pharma, Speakers bureau: Astellas Pharma, Manabu Iwasaki: None declared, Yeong Wook Song: None declared, Yi-Hsing Chen Speakers bureau: Astellas Pharma, Mitsuhiro Rokuda Employee of: Astellas Pharma, Inc., Hiroyuki Izutsu Employee of: Astellas Pharma, Inc., Satoshi Ushijima Employee of: Astellas Pharma, Inc., Yuichiro Kaneko Employee of: Astellas Pharma, Inc., Teruaki Shiomi Employee of: Astellas Pharma, Inc., Emi Yamada Employee of: Astellas Pharma, Inc.